1. y=x^2-5x+6.......eq(i)
y= -2x+6............eq(ii)
Therefore,
x^2-5x+6= -2x+6
x^2-5x+2x+6-6=0
x^2-3x=0
x(x-3)=0
either
x=0
or
x-3=0
=>x=3
putting the value of x in eq(ii)
either,
y= -2*0+6
y=6
or,
y=-2*3+6
y=-6+6
y=0
therefore,
when x=0, y=6
when x=3, y=0
2. y=-x^2+3x+2.......eq(i)
y= x-1............eq(ii)
Therefore,
-x^2+3x+2= x-1
-x^2+3x-x+2+1=0
-x^2+2x+3=0
x^2-2x-3=0
x^2-3x+x-3=0
x(x-3)+1(x-3)=0
(x-3)(x+1)=0
either
x-3=0
x=3
or
x+1=0
=>x=-1
putting the value of x in eq(ii)
either,
y= 3-1
y=2
or,
y=-1-1
y=-2
therefore,
when x=3, y=2
when x=-1, y=-2
2007-03-17 05:13:17
·
answer #1
·
answered by Bubblez 3
·
0⤊
0⤋